Prospective Study of BK Virus Infection in Patients with Inflammatory Bowel Disease - Virginia Flores; Belén Rodríguez-Sánchez; Ignacio Marín-Jiménez; Emilio Bouza; Luis Menchén; Patricia Muñoz (The Scientific World Journal)
Patients with inflammatory bowel disease (IBD) have an immune-deficient baseline status further modulated by immunosuppressive therapy that may promote the reactivation of latent viruses such as BK virus (BKV). The aim of this prospective study was to determine the prevalence of BKV infection in IBD patients and its potential relationship with the immunosuppressive treatment. Paired urine and plasma samples from 53 consecutive patients with IBD and 53 controls were analyzed. BKV detection was performed by conventional PCR and positive samples were further quantified by real-time PCR. No viremia was detected. BKV viruria was significantly more common in IBD patients than among the controls (54.7% versus 11.3%; P<0.0001). The only risk factor for BKV viruria in IBD was age (47.2±16.3 versus 37.8±15.2; P=0.036), and there was a trend towards higher rate of viruria in outpatients (61.5% versus 38.5%; P=0.096) and in those not receiving ciprofloxacin (59.5% versus 40.5%; P=0.17). A clear impact of the immunosuppressive regimen on BKV infection could not be demonstrated.